2009
DOI: 10.1039/b908688a
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-bonded multilayer of pH-responsive polymeric micelles with tannic acid for surface drug delivery

Abstract: We report the design of a platform for the delivery of hydrophobic drugs conjugated to block copolymer micelles via pH-responsive linkage that are assembled within hydrogen bonded polymer multilayer thin films.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
112
1
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 147 publications
(118 citation statements)
references
References 28 publications
(41 reference statements)
3
112
1
2
Order By: Relevance
“…20,26 Applications envisioned for such drug-loaded films include antimicrobial-or anti-inflammatory coatings on implants and drug-releasing coatings for stents. 24,27,28 Given the ability of multilayers to be conformally coated on a broad range of substrates, to load both small-molecule and macromolecular drugs, and to regulate the release of drugs over a period of hours to days, we became interested in the potential of these polyelectrolyte films in a new application area: transcutaneous drug delivery. Skin is an attractive site for non-invasive delivery of therapeutics, due to the ease of access to this organ and the ability of transcutaneous delivery to limit first-pass drug metabolism and alter the pharmacokinetics and pharmacodynamics of drugs.…”
mentioning
confidence: 99%
“…20,26 Applications envisioned for such drug-loaded films include antimicrobial-or anti-inflammatory coatings on implants and drug-releasing coatings for stents. 24,27,28 Given the ability of multilayers to be conformally coated on a broad range of substrates, to load both small-molecule and macromolecular drugs, and to regulate the release of drugs over a period of hours to days, we became interested in the potential of these polyelectrolyte films in a new application area: transcutaneous drug delivery. Skin is an attractive site for non-invasive delivery of therapeutics, due to the ease of access to this organ and the ability of transcutaneous delivery to limit first-pass drug metabolism and alter the pharmacokinetics and pharmacodynamics of drugs.…”
mentioning
confidence: 99%
“…On the other hand, tannin coatings can exhibit antibacterial, antimutagenic or antimicrobial effects [18][19][20]. There has also been an increasing interest in H-bonded assembly of tannic acid with several neutral polymers, including poly(Nvinylpyrrolidone), for the development of physiologically stable thin films and hollow capsules for controlled drug release (since tannin can be a model polyphenolic drug) and other biotechnology applications [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Biofilm encroachment on biomaterial is an important concern postsurgery. In the past, several studies of modifying surfaces have shown that pH-sensitive polyelectrolyte multilayers can be effectively used to release therapeutics at a specific pH (24,46). Drugs are incorporated within weak polyelectrolyte assemblies at low pH due to hydrogen bonding of the small molecule with the matrix to form thin multilayers.…”
mentioning
confidence: 99%